A holistic approach to the palaeoecology of Las Hoyas Konservat-Lagerstätte (La Huérguina Formation, Lower Cretaceous, Iberian Ranges, Spain) - Fregenal-martínez, M.A.; Buscalioni, A.D. (Journal of Iberian Geology, 2010)
The Las Hoyas fossil site (Lower Cretaceous, Iberian Ranges, Spain) is a classic lacustrine Fossil-Lagerstätte that exemplifies the features predicted by the original concept of Konservat Lagerstätten in relation to the quantity of remains, quality of preservation, completeness, and preservation by a combination of obrution, stagnation and, in this case, mainly bacterial sealing. Fossils are preserved in rhythmically laminated limestones deposited in a environment that underwent strong, climatically driven cyclical oscillations in water level within the framework of a seasonal, subtropical, regional-scale wetland. Extensive systematic layer-bylayer excavation and geological research have resulted in a comprehensive understanding of the stratigraphy and sedimentology of the locality and its regional palaeogeography. Two approaches have allowed the palaeoecology of the fossil association to be reconstructed. Firstly, autoecological reconstructions of the fossil groups are supplemented by palaeoenvironmental reconstructions based on the sedimentology. This considers taphonomic features and the ecological structure of the whole association, including vegetation and animals. The organization of the ecosystem resembles that of extant lentic ecosystems. It is dominated by obligate aquatic and amphibious organisms; facultative terrestrial organisms are scarce. Several lines of evidence from flora and fauna indicate strong seasonality and water stress. The second approach is dynamic and aims to unravel the information transferred to the fossil record about ecological dynamics and evolution by combining stratigraphical and palaeontological information and integrating this in a spatial and temporal framework. This analysis illustrates that Las Hoyas has a significant facies bias, reflecting alternating wet and dry climatically controlled periods. The biotic response these wet and dry cycles produced a coupling of taphonomic and sedimentary processes that resulted in the characteristic cyclical arrangement of the stratigraphic and palaeontological record. Las Hoyas therefore represents a subtropical seasonal wetland impacted by cyclicity and ecological stress. This stress impeded shortterm ecological evolution and resulted in a stable ecosystem that lasted for thousands of years. The results of this study also have implications for the concept of Konservat-Lagerstätten and its limitations. Whereas the former approach considers Las Hoyas as a canon of minimally biased information (as it is a Konservat-Lagerstatte), the latter approach reveals the biased characteristics of the association. The study illustrates that although all Konservat-Lagerstätten share similar preservational mechanisms, the paleoecological information that contain may differ.